2018
DOI: 10.1007/s13300-018-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Fasting and Postprandial Blood Glucose in Overall Glycemic Control: Post Hoc Analysis of a Phase IV Randomized Trial

Abstract: IntroductionFew prospective clinical trials have investigated the role of fasting blood glucose (FBG) and/or postprandial glucose (PPG) in assessing overall glycemic control by using different insulin regimens. In the present post hoc analysis, we assessed the contribution of FBG and/or PPG in overall glycemic control in Chinese patients under insulin treatment.MethodsCLASSIFY is a phase IV, randomized, open-label, 26-week, parallel-arm, treat-to-target, multinational, controlled study in patients with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Recent studies of diabetes patients being administered insulin [20][21][22] and Glucagon like peptide-1 receptor agonists (GLP-1 RAs) 23 are a good complement to our research. These studies also revealed that BG plays a major role in the subgroup of patients with HbA1c levels > 8.5%, and the relative contribution of PPG decreased with increasing HbA1c (from 65.5% to 39.2%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies of diabetes patients being administered insulin [20][21][22] and Glucagon like peptide-1 receptor agonists (GLP-1 RAs) 23 are a good complement to our research. These studies also revealed that BG plays a major role in the subgroup of patients with HbA1c levels > 8.5%, and the relative contribution of PPG decreased with increasing HbA1c (from 65.5% to 39.2%).…”
Section: Discussionmentioning
confidence: 99%
“…BG predominated when HbA1c was ≥9and ≥ 10% in oral antidiabetic drug- and insulin-treated patients. Li et al 20 , 22 (2018) 81 (a) T2DM treated with insulin (b) LM25 and LM50 (c)Chinese, China ≥6.1 (a) 4-point blood glucose profile at least one day (b) high-carbohydrate test meals on day 1 and high-fat test meals on day 2 and their habitual diets on day 3 7.8 ± 1.4 PPG played a major role of patients with HbA1c < 8.5%. PPG’s contribution rate decreased with increasing HbA1c (from 65.5% to 39.2%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there are several clinical trials directly comparing the effects of LM25 and LM50 on fasting hyperglycemia, postprandial hyperglycemia, and HbA 1c [ 27 31 ]. Our study and the above studies all showed that LM50 was more effective than LM25 in reducing postprandial blood glucose after the morning and evening meals, reducing prandial blood glucose excursion or stabilizing blood glucose excursion during the daytime [ 24 ].…”
Section: Discussionmentioning
confidence: 99%